Learning from the past to build the future: multidisciplinary design process - Iuorio, Ornella (TECHNE - Journal of Technology for Architecture and Environment, 2021)
Multidisciplinary skills and knowledges were common in historical constructions. The necessity to rethink the way we design and realize our built environment in response to the climate change is requiring the re-convergence of knowledge. The development of multidisciplinary practices and digital communication platforms are enabling the new transition. The design and fabrication of shell is one the field, where the cross-over of knowledge is most evident. Digital technologies are facilitating experimentations of complex shell geometries, a wise use of materials, and the development of new construction processes. This paper explores the transformation of shell designs, and the importance of multiple actors, through the analysis of a shell prototype developed for an international context.